1999
DOI: 10.1177/0193723599232006
|View full text |Cite
|
Sign up to set email alerts
|

The Globe and Mail Coverage of the Winter Olympic Games

Abstract: This research is a content analysis by gender of the Globe and Mail ’s coverage of the Winter Olympic Games from 1924 to 1992. Variables examined with respect to gender included: size and type of article/picture, sport, location, and source of article. One-way ANOVA and ANOVA with a Student-Newman-Keuls procedure were used to determine if significant differences existed between the above indices. The study found that female athletes were under-represented when compared to male athletes and women were frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 15 publications
5
22
0
1
Order By: Relevance
“…Malec (1994) suggested that equity be determined by comparing media coverage to school Sport in Society 693 enrolment. Urquhart and Crossman (1999) used participation rates, while Pedersen (2002a) incorporated participation rates of high school athletes, the number of sports offered to each sex, and the female and male make-up of school enrolment. CrossFit does not track the gender of its membership so there is no way to determine how many males as compared to females workout at CrossFit facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Malec (1994) suggested that equity be determined by comparing media coverage to school Sport in Society 693 enrolment. Urquhart and Crossman (1999) used participation rates, while Pedersen (2002a) incorporated participation rates of high school athletes, the number of sports offered to each sex, and the female and male make-up of school enrolment. CrossFit does not track the gender of its membership so there is no way to determine how many males as compared to females workout at CrossFit facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research shows that media outlets frequently exclude female athletes from lead stories and headlines found in national sports media (Daniels, 2008;Daniels, 2009;Duncan, 1990;Hardin, Lynn, & Walsdorf, 2005;Kane, 1996;Koivula, 1999;Lapchik & Mathews, 1999;Leath & Lumpkin, 1992;Leath & Williams, 1991;Messner, 2002;Perdersen & Whisenant, 2003;Primm, Preuhs, & Hewitt, 2007;Weber & Carini, 2012). In spite of the all-pervasive nature of sports in American culture, media seem to ignore the significance, contribution of, and importance of inclusion for women athletes (Davis, 1997;Urquhart & Crossman, 1999). …”
Section: Significance Of the Researchmentioning
confidence: 99%
“…In particular, men's domination of sport in all of its facets (i.e., administrative posts, coaching positions) has created a male hegemonic social institution. Through numerous practices (i.e., inequitable media coverage, homologous reproduction) the primary stakeholders in sport participate in the maintenance of masculine hegemony (Urquhart & Crossman, 1999).…”
Section: Hegemonic Masculinitymentioning
confidence: 99%